Emotion regulation as a mediator in the relationship between social isolation and psychological distress among students with mobile phone addiction - Xu, Liu; Arshat, Zarinah; Ismail, Nellie; Lulu, Shi (Wolters Kluwer Medknow Publications, 2026)
Introduction: Smartphone addiction, emotional regulation, and social isolation (SI) are highlighted as key contributing factors to psychological distress (PD). The study investigates whether emotion regulation mediates the link between SI and PD among Chinese university students, and examines potential differences between family and friend isolation, considering cultural context. Methods: A cross-sectional survey was conducted in May 2024 and June 2024 with 1276 undergraduates (mean age = 19.94 years) in Henan Province, China, using purposive sampling. Participants completed validated measures of SI (family and friends), PD, smartphone addiction, and emotion regulation strategies. Partial Least Squares Structural Equation Modeling was used for analyzing the data. Results: Both family SI (β = −0.056, P < 0.05) and friend SI (β = −0.191, P < 0.05) were significantly associated with PD. Friend SI significantly influenced PD through inhibition (β = −0.081, P < 0.05), and a similar pattern was found for family SI (β = −0.043, P < 0.05). Inhibition significantly mediated these relationships, suggesting that students who suppress emotional expression may experience greater PD when socially isolated. Cognitive reappraisal showed no significant mediating effect (β = 0.002, P > 0.05; β = −0.001, P > 0.05). Conclusions: Inhibition, as a maladaptive strategy, may heighten PD among socially isolated students with smartphone addiction. Improving adaptive regulation techniques may provide some protection. The findings support the development of targeted interventions to improve students’ emotion regulation skills and reduce psychological risks in excessive smartphone use and socially disconnected contexts.